Re-description and evolutionary remarks on the Patagonian horned turtle Niolamia argentina Ameghino, 1899 (Testudinata, Meiolaniidae) - Sterli, Juliana (2011)
The main objective of this paper is to undertake a detailed re-description of the neotype (skull and lower jaw) and the referred material (postcranial remains) of Niolamia argentina. Additional preparation of this material has revealed previously unrecognized details of the cranial and postcranial skeleton, including the recognition of additional cranial scales, bone sutures, and foramina, the presence of a distinct ornamentation on the skull roof, and the identification of several new inner skull structures. Importantly, the additional preparation shows detailed carotid artery anatomy: The entrance of the carotid artery lies posteriorly in the pterygoids, runs anteriorly and bifurcates into the cerebral and palatine arteries within the basisphenoid, and is not covered ventrally by the pterygoids. In addition, the pterygoids are placed in a ventral position with respect to the basisphenoid and an intrapterygoid slit, a character diagnostic of Meiolaniidae, is present. We corroborate that Crossochelys corniger is a junior synonym of Nio. argentina. Following our preferred phylogenetic hypothesis, South American and Australian taxa related to or belonging to Meiolaniidae and Mongolochelys efremovi from the Upper Cretaceous of Mongolia form a monophyletic group, implying that the origin and diversification of this lineage predated the complete break up of Pangea in the Early to Middle Jurassic. The presence of a ghost lineage between this clade and Cryptodira, extending from the Middle Jurassic to the Early Cretaceous, supports this assessment.